Assistance with Legal Documentation, Operational SOP, and Digital Marketing for the Tumbas Mindo Laren Cafe - Alifia Indriyani Nur Faizah; Widuri Octavianunisa; Arya Zaky Firmansyah; Abdul Majid (Trescode Green Organization, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth; however, many business owners still face challenges related to business legality, operational management, and the use of digital marketing. This community service activity aims to analyze the obstacles faced by the Tumbas Mindo Café, a micro, small, and medium enterprise located in Laren Subdistrict, Lamongan Regency, in order to increase brand awareness. This assistance program has a positive impact on operational effectiveness and the expansion of promotional reach through support in establishing business legality, as well as the development of written Standard Operating Procedures (SOPs), which can improve business outcomes by implementing digital marketing strategies via social media platforms such as Instagram and TikTok. This mentoring can yield results such as established business legality, better-managed social media, and more focused human resource management; when integrated, these elements can enhance the professionalism of business management and strengthen the sustainable competitiveness of micro, small, and medium enterprises.